2003
DOI: 10.1007/s007950300002
|View full text |Cite
|
Sign up to set email alerts
|

Histological classification of ovarian cancer

Abstract: The histology of ovarian tumors exhibits a wide variety of histological features. The histological classification of ovarian tumors by the World Health Organization (WHO) is based on histogenetic principles, and this classification categorizes ovarian tumors with regard to their derivation from coelomic surface epithelial cells, germ cells, and mesenchyme (the stroma and the sex cord). Epithelial ovarian tumors, which are the majority of malignant ovarian tumors, are further grouped into histological types as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
155
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(165 citation statements)
references
References 32 publications
3
155
0
7
Order By: Relevance
“…Kallikreins 6 and 13 are expressed in normal epithelium (Petraki et al, 2001(Petraki et al, , 2003, including the OSE as we have shown here. Ovarian cancer is thought to arise from either OSE or OSE cells bordering inclusion cysts (Kaku et al, 2003), therefore it is expected that ovarian cancer cells would express a basal level of kallikrein expression. Given the semi-quantitative nature of immunohistochemistry and the fact that KLKs are secreted proteins, to see a significant difference in the cellular levels between normal OSE and ovarian cancer would require not only changes in KLK protein production, but also a significant change in the rate of kallikrein exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kallikreins 6 and 13 are expressed in normal epithelium (Petraki et al, 2001(Petraki et al, , 2003, including the OSE as we have shown here. Ovarian cancer is thought to arise from either OSE or OSE cells bordering inclusion cysts (Kaku et al, 2003), therefore it is expected that ovarian cancer cells would express a basal level of kallikrein expression. Given the semi-quantitative nature of immunohistochemistry and the fact that KLKs are secreted proteins, to see a significant difference in the cellular levels between normal OSE and ovarian cancer would require not only changes in KLK protein production, but also a significant change in the rate of kallikrein exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…EOCs are commonly classified according to histopathological appearance as clear cell, endometrioid, mucinous or serous; amongst these, serous epithelial tumours are the most commonly diagnosed tumour type . However, wide varieties of less common ovarian neoplasms exist and can include mixed, undifferentiated or Brenner-type tumours (Kaku et al 2003, Arnogiannaki et al 2011. While traditionally subgrouped according to FIGO stage and grade, a growing body of evidence now suggests that low-and high-grade tumours have different aetiologies arising from unrelated, underlying molecular pathologies (Gilks et al 2008.…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%
“…Chemotherapy resistance is a major cause of metastasis and recurrence. EOC accounts for 85-90% of clinical ovarian malignancies, and SOC is the main type of EOC (45). At present, excision repair cross-complementing rodent repair deficiency, complementation group 1 (ERCC1) is a key topic of studies attempting to predict chemotherapy resistance in ovarian cancer (46,47).…”
Section: Discussionmentioning
confidence: 99%